Temporally and spectrally multiplexed single photon source using quantum feedback control for scalable photonic quantum technologies. (25th June 2018) - Heuck, Mikkel; Pant, Mihir; Englund, Dirk R
Abstract: Current proposals for scalable photonic quantum technologies require on-demand sources of indistinguishable single photons with very high efficiency. Even with recent progress in the field there is still a significant gap between the requirements and state of the art performance. Here, we propose an on-chip source of time-multiplexed, heralded photons. Using quantum feedback control on a photon storage cavity with an optimized driving protocol, we estimate an on-demand efficiency of 99% and unheralded loss of order 1%, assuming high efficiency detectors and intrinsic cavity quality factors of order 10 8 . We further explain how temporal- and spectral-multiplexing can be used in parallel to significantly reduce device requirements if single photon frequency conversion is possible with efficiency in the same range of 99%.